China in the global economy - Sunanda Sen (Levy Economics Institute of Bard College, 2010)
China occupies a unique position among developing countries. Its success in achieving relative stability in the financial sector since the institution of reforms in 1979 has given way to relative instability since the beginning of the current global financial crisis. Over the last few years, China has been on a path of capital account opening that has drawn larger inflows of capital from abroad, both foreign-direct and portfolio investment. Of late, a surge in these inflows has introduced problems for the monetary authorities in continuing with an autonomous monetary policy in China, especially with large additions to official reserves, the latter in a bid to avoid further appreciation of the country's domestic currency. Like other developing countries, China today faces the impossible trilemma of managing the exchange rate with near-complete capital mobility and an autonomous monetary policy. Facing problems in devising and sustaining this policy, China has been using expansionary fiscal policy to tackle the impact of shrinking export demand. The recent drive on the part of Chinese authorities to boost real demand in the countryside and to revamp the domestic market shows a promise far different from that of the financial rescue packages in many advanced nations. The close integration of China with the world economy over the last two decades has raised concerns from different quarters that relate both to (1) the possible effects of the recent global downturn on China and (2) the second-round effects of a downturn in China for the rest of world.
Keywords: P31; P33; P34; P45; Q53; 330; trade surplus; official reserves; impossible trillemma; integration; capital account opening; financial crisis; state-owned enterprises; stock markets; volatility; Globalisierung; Internationale Wirtschaftsbeziehungen; Kapitalmobilität; Währungsreserven; Wechselkurspolitik; Kapitalbilanz; China